2019
DOI: 10.1016/j.ijpharm.2019.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Hot-melt extrusion process impact on polymer choice of glyburide solid dispersions: The effect of wettability and dissolution

Abstract: The utilising of innovative combinatorial chemistry and high-throughput screening tools in drug discovery has led to more active pharmaceutical ingredients with poorly soluble properties reaching clinical stages of drug development processes. It is estimated that two out of five pharmaceutical compounds in the US market are considered poorly soluble (Fahr & Liu, 2007). Poorly soluble drugs are very challenging during pharmaceutical development as solubility, and further dissolution tends to be the rate-limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Since both polymer type and drug loading may affect viscosity of the molten mixture in the extruder, both may affect cavity formation by changing viscosity. This result agrees well with the similar void-forming phenomena reported in the literature (Alshafiee et al, 2019, Martinez-Marcos et al, 2016, Fukuda et al, 2006. In addition to the differences observed in the numbers of voids in the extrudates with different drug loadings, the diameters of the extrudates also increases with increasing the drug content and the screw speed, as shown in Figure 7.…”
Section: Effect Of Viscositysupporting
confidence: 92%
See 1 more Smart Citation
“…Since both polymer type and drug loading may affect viscosity of the molten mixture in the extruder, both may affect cavity formation by changing viscosity. This result agrees well with the similar void-forming phenomena reported in the literature (Alshafiee et al, 2019, Martinez-Marcos et al, 2016, Fukuda et al, 2006. In addition to the differences observed in the numbers of voids in the extrudates with different drug loadings, the diameters of the extrudates also increases with increasing the drug content and the screw speed, as shown in Figure 7.…”
Section: Effect Of Viscositysupporting
confidence: 92%
“…However, recently a number of studies reported the use of additives, such as disintegrants and other particulate excipients that form a separate phase to the drug dispersion (Fukuda et al, 2006, Alqahtani et al, 2020, Deng et al, 2013, Krupa et al, 2017, Sadia et al, 2018, Sadia et al, 2016, Crowley et al, 2004. Occasionally, voids were observed in extrudates (Alqahtani et al, 2020, Alshafiee et al, 2019, Fukuda et al, 2006, Martinez-Marcos et al, 2016, Almeida et al, 2011, Crowley et al, 2004. We specifically term such structural features as voids rather than pores because they typically are isolated pockets in the interior of the extrudates and they are not, in most cases, apparent on the surface of the extrudates.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 also shows that porosity was present in all cores after melt molding. Porosity has been observed previously in melt-extruded VA64 filaments [ 78 ]. However, unlike the applied force exerted by the screws during mixing in melt extrusion, we postulate that the melt molding process, which involved loose stacking of filament sections in the cup followed by melting without any applied force, was likely to contribute more to eventual core porosity.…”
Section: Resultsmentioning
confidence: 57%
“…Kolliphor ® P 407 is a triblock polymer composed of a central block of hydrophobic polypropylene oxide (PPO) surrounded by two hydrophilic blocks of polyethyleneoxide (PEO). The molecular weight of this polymer is in the range of 9840-14600 daltons [14,15]. It shows the phenomena of micellization due to its amphiphilic nature [16].…”
Section: Introductionmentioning
confidence: 97%